2012
DOI: 10.1186/1742-2094-9-100
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal correlation in progressive degeneration of neurons and astrocytes in contusion-induced spinal cord injury

Abstract: BackgroundTraumatic spinal cord injury (SCI) causes acute neuronal death followed by delayed secondary neuronal damage. However, little is known about how microenvironment regulating cells such as microglia, astrocytes, and blood inflammatory cells behave in early SCI states and how they contribute to delayed neuronal death.MethodsWe analyzed the behavior of neurons and microenvironment regulating cells using a contusion-induced SCI model, examining early (3–6 h) to late times (14 d) after the injury.ResultsAt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
65
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 69 publications
4
65
0
2
Order By: Relevance
“…Surprisingly, only a small extension of PhMN loss was observed over time, despite the progressive increase in lesion volume beyond 1 DPI. Consistent with our observations and other work, 2,15 Andrade and colleagues showed that secondary neurodegeneration is pronounced following moderate SCI, unlike following more severe injury. 18 In our current study, the secondary degenerative process may have been minimized because of the severity of the initial 395 kD impact.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Surprisingly, only a small extension of PhMN loss was observed over time, despite the progressive increase in lesion volume beyond 1 DPI. Consistent with our observations and other work, 2,15 Andrade and colleagues showed that secondary neurodegeneration is pronounced following moderate SCI, unlike following more severe injury. 18 In our current study, the secondary degenerative process may have been minimized because of the severity of the initial 395 kD impact.…”
Section: Discussionsupporting
confidence: 82%
“…10 Our study demonstrates that following unilateral C4 contusion SCI, PhMN loss in the ipsilateral phrenic nucleus primarily occurs within the first 24 h post-injury. Very early loss of motor neurons (i.e., between 12 and 24 h post-injury) has already been shown in thoracic contusion models, [15][16][17] further suggesting that therapeutic interventions targeting motor neuron sparing should be delivered within 1 DPI. Surprisingly, only a small extension of PhMN loss was observed over time, despite the progressive increase in lesion volume beyond 1 DPI.…”
Section: Discussionmentioning
confidence: 99%
“…However, we and others have reported that brain inflammation is not neurotoxic but is instead neuroprotective and functions to repair the injured brain (Batchelor et al, 1999; Elkabes et al, 1996; Howe and Barres, 2012; Jeong et al, 2010; 2013a; 2013b; Kim et al, 2010; Koch and Szecsey, 2000; Lehrmann et al, 1998; Min et al, 2012; Reines et al, 2004; Scharf et al, 1999; van Gool et al, 2003; Vinet et al, 2012; Yang et al, 2007). In this study, we demonstrated that inflammatory responses were similar in both KA-and NMDA-injected cortexes.…”
Section: Discussionmentioning
confidence: 78%
“…Thus, astrocyte support is required for neuronal survival (Jeong et al, 2013c; Min et al, 2012). A loss of EAAT2/GLT-1 and decreased glutamate transport have been identified in human ALS patients (Rothstein et al, 1992; 1995).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the microglia died prior to the neurons in the penumbra region, where the delayed neuronal death occurs [2, 35]. We previously reported that LPS did not induce neuronal death in the cortex but induced it slowly in the SN, where astrocytes density was high and low, respectively [35].…”
Section: Discussionmentioning
confidence: 99%